Evolution of ANT family and regulation of lint percentage by the GhAIL6-GhTPL1 module - Xu, Jiwen; Chen, Xiaoping; Du, Junjie; Liu, Zhijuan; Zhang, Tianzhen (Frontiers in Plant Science, 2025)
IntroductionThe AINTEGUMENTA/AINTEGUMENTA-like (ANT/AIL) family belongs to the APETALA 2/ETHYLENE RESPONSE FACTOR superfamily and plays a key role in regulating numerous developmental processes. Only limited research has been conducted on the ANT family in upland cotton (Gossypium hirsutum L.), despite upland cotton’s global importance as a major source of renewable textile fibers. Elucidating the mechanism of ANT/AILs in cotton fiber development is crucial for the breeding of high-yield cotton.MethodsUsing phylogenetic trees explored the evolution of the ANT family. Using RNA sequencing data analyzed the expression of ANT/AILs in different cotton tissues. Using yeast two-hybrid (Y2H), dual-luciferase complementation assay (LUC) and bimolecular fluorescence complementation (BiFC) explored the interaction protein with GhAIL6. Using CRISPR-cas9 technology explored the regulation of GhAIL6-GhTPL1 module.ResultsThe ANT family originated in Bryophytes. A rapid expansion of ANT members occurred in the common ancestor of angiosperms, with the total number remaining stable in both Monocots and Eudicots. Cotton contained 20 ANT genes, as a duplication event in its ancestors led to expansion of AIL6/AIL7. Editing of GhAIL6 and GhTPL1 in upland cotton demonstrated AIL6-TPL1 module to regulate seed index (SI) and lint percentage (LP). Y2H, LUC and BiFC supported the interaction between GhAIL6 and GhTPL1.DiscussionOverall, this study offered a novel insight into the evolutionary dynamics of ANT family members and length. Edited cotton lines of GhAIL6 and GhTPL1, LP was significantly higher than in the control group, and SI significantly lower than in the control group. This study provided a new GhAIL6-GhTPL1 module for high-yield cotton breeding.